Africa's Pulse, April 2010 : An Analysis of Trends Shaping Africa's Economic Future - World Bank (Washington, DC, 2014)
This Africa's pulse newsletter includes the following headings: recent economic trends and prospects; Africa and the millennium development goals; and yes Africa can: success stories from a dynamic continent.